EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN PENDEKATAN ISLAM DALAM MENINGKATKAN CURIOSITY SISWA - Anisatun Murtafiah (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2023)
This study aims to determine the effectiveness of group guidance services with an Islamic approach in increasing students' curiosity. This study uses a type of experimental quantitative research, and the data source comes from 27 students with a data collection method in the form of a questionnaire. The data analysis technique in this study used SPSS version 22.0 with the Shapiro-Wilk test, which obtained a sig. (2-tailed) and interpretation of the results using the paired sample test. The results of this study indicate that there is an increase in the results of the post-test. So it can be concluded that Ho is rejected Ha is accepted.